Linear field dependencies of conductivity and phonon-induced conductivity of 2D gas in δ-doped GaAs - Slutskii, M.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The electrical field dependencies of current I and its variation under phonon pulses - ΔIph, were measured in δ-doped GaAs with n = 5*10¹¹ nm⁻². It was shown that if E< 1 V/cm and T = 2 K, E/I, and E/Iph linearly increase with E, and while the change in the first value was less than 5%, the second one increased by more than 3 times. The proposed explanation of experimental results is based on the nearness of the studied structure to a metal-insulator transition.